2013
DOI: 10.1074/jbc.m113.491431
|View full text |Cite
|
Sign up to set email alerts
|

Lactosylceramide Interacts with and Activates Cytosolic Phospholipase A2α

Abstract: Background:LacCer is known to regulate PLA 2 activity in cells, but the precise mechanisms have not been elucidated. Results: LacCer binds to cPLA 2 ␣ and increases its enzymatic activity. Conclusion: LacCer is identified as a novel and direct activator of cPLA 2 ␣. Significance: This research provides new insights into the regulatory mechanisms of cPLA 2 ␣ and the physiological functions of LacCer as a signaling molecule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 31 publications
3
34
0
Order By: Relevance
“…Our laboratory has reported recently that TNF-ainduced AA release is abolished by RNA interference of cPLA 2 a or glucosylceramide synthase (14). TNF-a induces the translocation of cPLA 2 a to the perinuclear regions, which is inhibited by treatment with inhibitor of glucosylceramide synthase.…”
Section: The Role Of Sphingolipid Metabolism In the Inflammatory Respmentioning
confidence: 99%
See 1 more Smart Citation
“…Our laboratory has reported recently that TNF-ainduced AA release is abolished by RNA interference of cPLA 2 a or glucosylceramide synthase (14). TNF-a induces the translocation of cPLA 2 a to the perinuclear regions, which is inhibited by treatment with inhibitor of glucosylceramide synthase.…”
Section: The Role Of Sphingolipid Metabolism In the Inflammatory Respmentioning
confidence: 99%
“…LacCer stimulates PECAM-1 (platelet endothelial cell adhesion molecule-1) expression in the adhesion and diapedesis of monocytes/ lymphocytes, which is inhibited by treatment with inhibitors of Ca 2+ -independent PLA 2 or cPLA 2 a (13). Recently, our laboratory has reported that down-regulation of cPLA 2 a using RNA interference abolishes the ability of LacCer to induce AA release in cells, suggesting that cPLA 2 a is the key PLA 2 downstream of LacCer (14). Treatment of cells with LacCer induces the translocation of full-length cPLA 2 a from the cytosol to the Golgi apparatus.…”
Section: Role Of Lactosylceramide (Laccer) In the Activity Of Cpla 2 Amentioning
confidence: 99%
“…1 ). Binding of cPLA 2 ␣ to the Golgi may, in part, involve interaction of the C2 domain with sphingolipids, including ceramide-1-P and lactosylceramide (93)(94)(95)(96). Translocation of cPLA 2 ␣ to membrane is necessary but not suffi cient for cPLA 2 ␣ to release arachidonic acid ( 92 ).…”
Section: Downloaded Frommentioning
confidence: 99%
“…For example, Cer produced by sphingosine kinase-1 is required for MDCK cell growth (29). LacCer induced ROS generation and activation of ERK1/2 in cardiomyocytes (30), Ras activation in human aortic smooth muscle cells (31), and PLA2a activation via direct binding (32). We speculate that various lipids and several signaling pathways are involved in the active K-Ras-induced phenotypes.…”
Section: Discussionmentioning
confidence: 99%